IoT-Based Smart Air Quality System: A Real-Time Monitoring Solution for Indoor Air Quality - Joni Candra; Hazimah (Information Technology and Science (ITScience), 2026)
Indoor Air Quality (IAQ) plays a crucial role in maintaining human health and comfort. This study aims to design and implement an Internet of Things (IoT)-based indoor air quality monitoring system integrated with a mobile application for real-time observation. The system employs sensors to measure environmental parameters such as temperature, humidity, and carbon dioxide (CO?) levels, with data transmitted wirelessly and visualized through the mobile app. The applied method includes hardware design, IoT-based software development, and system testing in several rooms with different activity conditions. The implementation results show that the system can accurately display air quality data and provide automatic notifications when pollutant levels increase. Based on seven days of measurement, the kitchen area indicated a “Poor Air” category, while the living room and bedroom were classified as “Fresh Air.” This system effectively delivers fast and accurate air quality information, enabling users to take preventive actions to maintain healthy indoor air conditions